RELATIONSHIP OF THE QURAN AND OTHER RELIGIOUS SCRIPTURES: Studies on al-Muhaymin in Q.S. al-MÃ¢idah 48 - Iman, Fuji Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This paper reviews the position of the Quran as al-Muhaymin toward the other religious scriptures. Specifically, the study focuses on Q.S. al-MÃ¢idah [5]: 48, which explicitly contains the word â€œal-muhayminâ€. That word in the mentioned surah triggers the polemics among mufassir and starts the discussion on its relation with the authenticity of the other previous holy books. Some relate the booksâ€™ authenticity with naskh and taá¸¥rÃ®f that leads to the claim of falsification within those books. By interpreting the word â€œal-muhayminâ€, the author attempts to objectively re-comprehend the bond between the Quran and the previous holy books. By tracing the classic and modern tafsÃ®r books, the author assumes that the Quran is the continuation of other books revealed by Allah in advance. The connection of the Quran and the previous books is as the sharia revealed by Allah to people with the similar universal principles. In this case, God and the principles within those books are the same, yet, it is formulated by the law which is dissimilar in the context. Both the Quran and the previous holy books have the same purpose that is to assure peopleâ€™s safety and happiness.